Juliet & Romeo [videorecording (DVD)] - Bogart, Timothy Scott; Rugaard, Clara, 1997-; Ward, Jamie (Actor); Isaacs, Jason, 1963-; Parx, Tayla; Folger, Dan (Actor); Podnay, Nicholas; Walsh-Peelo, Ferdia; Graves, Rupert, 1963-; Ortiz Luis, Martina; Grech, Alex; Andres, Dennis (Actor); et al. (Universal Pictures Home Entertainment, 2025)
A groundbreaking pop musical that reimagines the iconic tale of star-crossed lovers in a fresh, exhilarating way, blends timeless romance with original music. Set in 1301 and inspired by the real-life story behind Shakespeare's classic, with stunning choreography, vibrant visuals, and a modern twist, Juliet & Romeo captivates audiences with its unique fusion of love, music, and theatrical magic!